Awareness of Household Food Waste Management with A Zero-Waste Concept: A Preliminary Study - Aprilia, Anisa; Novi Haryati; Heptari Elita Dewi; Imaniar Ilmi Pariasa; Andrean Eka Hardana; Rachman Hartono; Djoko Koestiono; Effy Yuswita; Fitria Dina Riana; Silvana Maulidah; Dwi Laila Maulida; Usda Kristina Tassariya (HABITAT, 2022)
This is pilot study designed to ascertain college students' understanding of domestic food waste management using an online questioner. The descriptive results section of the report is used to describe the central tendency of the data collected for each variable. Meanwhile, the people who took part in the research were all part of a webinar on waste management that was led by people from universities and environmental groups. The findings indicated that students' knowledge of domestic food waste management remained diverse. Some of them continue to view waste management as a time-consuming and demanding activity.  Community understanding about waste management, especially food, should be given early and started at home. As a result, environmentally friendly activities must be regularly promoted and implemented at the school, university, government, and community levels in order to improve people's quality of life.